Pendampingan Pengujian Material agregat Kelas A di Dinas Pekerjaan Umum, Penataan ruang dan Pertanahan UPTD Peralatan dan Penguji Material Konstruksi Kabupaten Tanah Laut - Safitri, Intan; Kurniawan, Budi; Alam Sur, Widiya Astuti (Jurnal Masyarakat Indonesia (Jumas), 2025)
This service is assistance in testing activities for class A aggregates at the Public Works, Spatial Planning and Land Services UPTD Equipment and Construction Material Testing of Tanah Laut Regency. This assistance activity will be carried out for one month starting on September 2 2024. The theme of this service is Assistance with Testing of Class A aggregate materials at the Public Works, Spatial Planning and Land Services UPTD Equipment and Construction Material Testers, Tanah Laut Regency. This activity is intended as assistance in analyzing whether the quality of the class A aggregate material used meets SNI (Standar Nasional Indonesia) and knowing whether the CBR (California Bearing Ratio) test value of the class A aggregate material used meets the requirements of the 2018 General Bina Marga Specifications (Division 5). This service method is carried out in the form of assisting UPTD employees in several aggregate tests in accordance with the required specifications. The result of this assistance activity was that testing the specific gravity and dry weight of the saturated surface revealed that it did not meet the requirements for testing the specific gravity and absorption of coarse aggregate. Meanwhile, the results of testing the specific gravity and absorption of fine aggregate showed that the specific gravity, saturated surface dry weight, apparent specific gravity and water absorption were found to meet the requirements.